Impact of next generation sequencing on diagnostics in a genetic skin disease clinic. Issue 12 (December 2013) - Takeichi, Takuya; Nanda, Arti; Liu, Lu; Salam, Amr; Campbell, Patrick; Fong, Kenneth; Akiyama, Masashi; Ozoemena, Linda; Stone, Kristina L.; Al‐Ajmi, Hejab; Simpson, Michael A.; McGrath, John A.
Abstract Individuals with inherited skin diseases often pose one of the most difficult diagnostic challenges in dermatology. The hunt for the underlying molecular pathology may involve candidate gene screening or linkage analysis, which is usually determined by the initial history, the physical findings and laboratory tests. Recent technical advances in DNA sequencing, however, are shifting the diagnostic paradigm. Notably, next‐generation sequencing allows a more comprehensive approach to diagnosing inherited diseases, with potential savings of both time and money. In the setting of a paediatric dermatology genetics clinic in Kuwait, we therefore performed whole‐exome sequencing on seven individuals without a priori detailed knowledge of the patients' disorders: from these sequencing data, we diagnosed X‐linked hypohidrotic ectodermal dysplasia (two cases), acrodermatitis enteropathica, recessive erythropoietic protoporphyria (two siblings) and localized recessive dystrophic epidermolysis bullosa (two siblings). All these groups of disorders are clinically and genetically heterogeneous, but the sequencing data proved inherently useful in improving patient care and avoiding unnecessary investigations. Our observations highlight the value of whole‐exome sequencing, in combination with robust bioinformatics analysis, in determining the precise molecular pathology and clinical diagnosis in patients with genetic skin disorders, notably at an early stage in the clinical evaluation of these often complex disorders and thereby support a new paradigm for future diagnostics.